Dysmenorrhea. How to improve the quality of life? - A.A. Olina; T.A. Meteleva (LCC «Medicine-Inform», 2021)
A.A. Olina1,2, T.A. Meteleva3 1I.I. Mechnikov North-Western State Medical University, St. Petersburg, Russian Federation 2D.O. Ott Research Institute of Obstetrics, Gynecology, & Reproduction, St. Petersburg, Russian Federation 3Academician E.A. Vagner Perm State Medical University, Perm, Russian Federation Aim: to evaluate the rate of dysmenorrhea among secondary and high school students and to validate a differentiated treatment approach to hormonal contraception. Patients and Methods: 1,435 secondary and high school students of the city of Perm aged 18-25 years were interviewed over a 4-month period. 223 girls who complained of painful periods were examined (anthropometry, pain assessment using a visual analogous scale/VAS, and pelvic ultrasound). In addition, the rate of dysmenorrhea was assessed using the statistical form No. 12 "Data on the number of cases registered in the patients who are resident in the territory serviced by a medical organization". Results: according to official statistics, the rate of menstrual disorders (including dysmenorrhea) is 0.70-2.03%. The survey has demonstrated that 84.1% of students experience period pain. However, only 18.4% of them see a gynecologist. 63.2% experience pain for 2-3 days, 34% describe their pain as severe (VAS 7-10), and 29.1% are forced to take three or more NSAID pills daily. The symptoms of endometriosis were revealed in every tenth girl. A personalized choice of hormonal contraception allowed for the reduction in pain severity (none of the girls reported on severe pain, i.e., VAS 7-10), period duration, and heavy periods. Conclusions: official statistics does not illustrate the actual prevalence of dysmenorrhea. A personalized choice of hormonal contraception provides high compliance rate, the required duration of treatment, pain relief, the improvement of neuro-vegetative and metabolic processes and, as a result, a significant improvement in the quality of life. Keywords: dysmenorrhea, hormonal contraception, endometriosis, chronic pelvic pain, quality of life, drospirenone. For citation: Olina A.A., Meteleva T.A. Dysmenorrhea. How to improve the quality of life? Russian Journal of Woman and Child Health. 2021;4(1):46-52. DOI: 10.32364/2618-8430-2021-4-1-46-52.